Age as a Factor of Psychosexual Dysfunction and Marital Dissatisfaction among Heterosexual Married Individuals - Ilori , Stephen Oluyemi; Ogunleye, Adedeji Julius (African Journal of Stability and Development (AJSD), 2018)
This study was carried out to assess whether age will influence marital dissatisfaction and psychosexual dysfunction among heterosexual married individuals in Ado-Ekiti metropolis. A total number of 453 [(male = 188, Female = 265) participants with age range between 23 and 65 years] participated in the study using purposive sampling method. These participants completed a questionnaire that consists of the Golombok Rust Invention of Sexual Satisfaction (GRISS) by Golombok and Rust (1986), Index of Marital Satisfaction (IMS) by Hudson (1982). The results of data analyses indicated that age did not influence marital satisfaction and psychosexual dysfunction among males and females. Recommendation was made in this study that a regular psycho-education in form of marriage seminars should be periodically sponsored by government and nongovernmental organisations for the elderly married people with a view to addressing various problems that are capable of reducing active sexual activities of the aged people.